Arthropod diversity in two Historic Gardens in the Azores, Portugal - Arteaga, Alba (2020)
The aim of our study was to characterise and compare the richness and composition of endemic, native (non-endemic) and introduced arthropod assemblages of two Azorean Historic Gardens with contrasting plant species composition. We hypothesised that Faial Botanic Garden would hold higher arthropod diversity and abundance of native and endemic arthropod species due to its larger native plant community. Species were collected using several arthropod standardised techniques between April 2017 and June 2018. We used the alpha diversity metrics (Hill series) and the partitioning of total beta diversity (βtotal) into its replacement (βrepl) and richness (βrich) components, to analyse the adult and total arthropod community. The orders Araneae, Coleoptera and Hemiptera were also studied separately. Our results show that the number of exotic arthropod species exceeds the number of native and/or the endemic species in both gardens, but the arthropod community of Faial Botanic Garden exhibited a higher density of endemic and native species. Despite some minor exceptions, the geographic origins of plant communities largely influenced the arthropod species sampled in each garden. This study improves our knowledge about urban arthropod diversity in the Azores and shows how well-designed urban garden management and planning contribute to the conservation of native and endemic Azorean species.